Aus Trotzkopf's Ehe - Wildhagen, Else, 1861-1944; Planck, Willy, 1870-1956 (Salt Lake City, UT : Project Gutenberg, 2012)
"AUS TROTZKOPF's EHE" by Else Wildhagen is a novel written in the late 19th century. The book seems to explore the lives of various characters, prominently featuring Onkel Heinz, a professor known for his quirky interactions with children and adults alike, and Ilse, a lively and imaginative woman. Through a series of domestic scenes and personal relationships, it likely captures the dynamics of family life, friendship, and societal expectations of the time. The opening of the novel introduces readers to a warm domestic scene where children enthusiastically interact with Onkel Heinz, demonstrating his role as a beloved figure among them. The interactions between the characters, including Ilse and her friend Nellie, provide insights into their personalities and relationships. Onkel Heinz's humorous yet somewhat cantankerous nature is highlighted, along with Ilse's spiritedness and desire for adventure. As the narrative unfolds, it captures their joy, the simplicity of their everyday lives, and hints at deeper themes of personal growth and social commentary, setting the tone for the experiences and challenges they will face together. (This is an automatically generated summary.)
Release date is 2012-04-02
Keywords: Marriage -- Germany -- Fiction